Characterization of entangled photon pairs generated by a PPKTP crystal (2023)
The Periodically Poled Potassium Titanyl Phosphate (PPKTP) is a type of non linear crystal that serves as a source of production of entangled pairs of photons. The produced pair of photons, known as the Signal and Idler photons, possess unique characteristics within their entanglement that allow the production of new technologies such as quantum cryptography and quantum teleportation. The creation of the Signal and Idler photons occur through a process named Spontaneous Parametric Down Conversion (SPDC), which occurs when the pump laser beam penetrates a non linear medium. SPDC follows conservation of momentum and energy, thus imposing phase matching conditions on the generated photon pairs. These conditions result in specific space and frequency correlations of the photons. The aim of this project is to characterize the entangled photon pairs in their spatial profile and frequency spectrum, known as the Joint Spectrum.